The Acceptability and Feasibility of a Preschool Intervention Targeting Motor, Social, and Emotional Development - James, Maeghan E.; Bedard, Chloe; Bremer, Emily; Cairney, John (Frontiers in Pediatrics, 2020)
Background: Children and youth are facing three major challenges: (1) poor mental health, (2) physical inactivity and (3) lack of school readiness. Fundamental movement skills (FMS) and social-emotional learning (SEL) are two developmental domains that are associated with each of these challenges. Currently, there is little focus on interventions that target both FMS and SEL. Thus, the purpose of this study was to: (1) examine the acceptability and feasibility of an FMS and SEL program (Move 2 Smile), and (2) assess the impact of Move 2 Smile on FMS and SEL in children. Methods: An exploratory, pilot study using a within-subjects design was conducted. Descriptive statistics were computed to assess the acceptability and feasibility of the Move 2 Smile program. Changes in FMS and SEL were analyzed using a paired sample t-test. A focus group was conducted with parents to gain feedback after the program ended. Results: 11 children (4 girls, Mage = 50.56 mo, SD = 8.63) participated with families attending 80% of the sessions. Children and parents rated the enjoyment of the program 4.1/5 and 4.7/5, respectively. The instructor rated the children’s perceived enjoyment 4.6/5 and feasibility of the sessions 4.7/5. Parents engaged in the FMS take home activities one time per week and the SEL activities three times per week. The intervention had a non-significant small to medium effect on FMS (dz = .42, p = .19), a significant large effect on social skills (dz = 1.38, p = .001) and emotion expressiveness (dz = .79, p = .03) and a non-significant small to medium effect on emotion knowledge (dz = .58, p = .10) and emotion regulation (dz = .44, p = .17). Results from the focus group suggest that parents and children enjoyed the program and that the program was useful and effective at impacting FMS and SEL. Conclusions: This intervention is one of the first to intentionally target both FMS and SEL. Children, parents, and instructors deemed this program as acceptable and feasible. These preliminary findings warrant future evaluations of Move 2 Smile, including a randomized controlled trial.